Geometrie-Stereometrie-Kreiskegel


  • $V = \frac{1}{3}\cdot r^{2} \cdot \pi \cdot h$
    1 2
    $r = \sqrt{\frac{3\cdot V}{\pi \cdot h}}$
    1
    $h = \frac{3\cdot V}{r^{2} \cdot \pi }$
    1
    $O = r\cdot \pi \cdot (r+s)$
    1
    $s = \frac{ O}{r\cdot \pi } - r$
    1 2 3
    $r = \frac{-\pi \cdot s + \sqrt{(\pi \cdot s)^{2} +4\cdot \pi \cdot O}}{ 2\cdot \pi }$
    1 2 3
    $M = r\cdot \pi \cdot s$
    $s = \frac{ M}{r\cdot \pi }$
    1 2 3 4
    $r = \frac{ M}{s\cdot \pi }$
    1 2 3 4 5
    $s =\sqrt{h^{2} + r^{2} }$
    1
    $r =\sqrt{s^{2} - h^{2} }$
    1
    $h =\sqrt{s^{2} - r^{2} }$
    1

Beispiel Nr: 01
$ \text{Gegeben:}\\\text{Mantellinie} \qquad s \qquad [m]\\ \text{Radius} \qquad r \qquad [m] \\ \\ \text{Gesucht:} \\ \text{Höhe} \qquad h \qquad [m] \\ \\ h =\sqrt{s^{2} - r^{2} }\\ \textbf{Gegeben:} \\ s=6m \qquad r=4m \qquad \\ \\ \textbf{Rechnung:} \\ h =\sqrt{s^{2} - r^{2} } \\ s=6m\\ r=4m\\ h =\sqrt{(6m)^{2} - (4m)^{2} }\\\\h=4,47m \\\\\\ \small \begin{array}{|l|} \hline r=\\ \hline 4 m \\ \hline 40 dm \\ \hline 400 cm \\ \hline 4\cdot 10^{3} mm \\ \hline 4\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline s=\\ \hline 6 m \\ \hline 60 dm \\ \hline 600 cm \\ \hline 6\cdot 10^{3} mm \\ \hline 6\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline h=\\ \hline 4,47 m \\ \hline 44,7 dm \\ \hline 447 cm \\ \hline 4,47\cdot 10^{3} mm \\ \hline 4,47\cdot 10^{6} \mu m \\ \hline \end{array}$